Komunikasi Transendental Usif Boti dalam Ritual Halaika dan Pembentukan Harmoni Komunitas - Andung, Petrus Ana; Nope, Hotlif Arkilaus; Doko, Meryana Micselen (Fakultas Ilmu Komunikasi UKWMS, 2025)
ABSTRACT The Boti Dalam indigenous community in South Central Timor Regency, East Nusa Tenggara Province, continues to uphold the traditional Halaika belief system, which positions the Usif (king) Boti as both the spiritual leader and the guardian of social order. The study aims to explore the forms and meanings of the Usif Boti’s transcendental communication within Halaika rituals and to examine its contribution to maintaining social order and community harmony. The research adopts a constructivist paradigm with an ethnographic approach, and the data were collected through participant observation and in-depth interviews with the Boti King, community leaders, and members of the Boti Dalam community. The findings show that the Usif Boti’s transcendental communication is expressed through prayers and decrees addressed to Uis Neno (the sky deity) and Uis Pah (the earth deity) across various stages of life, particularly within the agricultural cycle. This form of communication is regarded as a sacred invocation that carries spiritual and moral legitimacy, and is therefore followed by all members of the Boti Dalam community. Through rituals such as onen (prayer), including the ninth-day observance (neon leuf) and the harvest thanksgiving (poi pah), the Usif Boti’s transcendental communication functions as a symbolic force that unites the community, sustains social order, and reinforces the value of fraternal love (lais manekat). The study concludes that the transcendental communication of the Usif Boti plays a central role as a symbolic instrument that supports social and economic harmony and order within the Boti Dalam community. ABSTRAK Masyarakat adat Boti Dalam di Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur, masih mempertahankan sistem kepercayaan tradisional Halaika yang menempatkan Usif (raja) Boti sebagai pemimpin spiritual sekaligus penjaga keteraturan sosial. Tujuan penelitian antara lain mengeksplorasi bentuk dan pemaknaan komunikasi transendental Usif Boti dalam ritual Halaika, serta menelaah kontribusinya dalam membangun keteraturan sosial dan harmoni komunitas. Paradigma penelitian yang digunakan adalah konstruktivistik dengan pendekatan etnografi, dan data dihimpun melalui observasi partisipan serta wawancara mendalam dengan Raja Boti, tokoh masyarakat, serta warga Boti Dalam. Hasil kajian menunjukkan bahwa komunikasi transendental Usif Boti terwujud melalui doa dan titah yang dipersembahkan kepada Uis Neno (dewa langit) dan Uis Pah (dewa bumi) dalam berbagai tahapan kehidupan, khususnya dalam siklus pertanian. Komunikasi transendental Usif Boti dikonstruksi sebagai doa sakral yang mengandung legitimasi spiritual dan moral, sehingga ditaati oleh seluruh warga masyarakat Boti Dalam. Melalui ritual seperti onen (sembahyang) baik pada momentum hari kesembilan (neon leuf), maupun syukuran panen (poi pah), komunikasi transendental Usif Boti berfungsi sebagai simbol yang mengikat komunitas, menjaga keteraturan sosial, serta meneguhkan nilai kasih persaudaraan (lais manekat). Penelitian ini menyimpulkan bahwa komunikasi transendental Usif Boti memiliki peran sentral sebagai instrumen simbolik yang dapat menopang harmoni dan keteraturan sosial dan ekonomi dalam masyarakat Boti Dalam.